2019
DOI: 10.1186/s40425-019-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Monalizumab: inhibiting the novel immune checkpoint NKG2A

Abstract: The implementation of immune checkpoint inhibitors to the oncology clinic signified a new era in cancer treatment. After the first indication of melanoma, an increasing list of additional cancer types are now treated with immune system targeting antibodies to PD-1, PD-L1 and CTLA-4, alleviating inhibition signals on T cells. Recently, we published proof-of-concept results on a novel checkpoint inhibitor, NKG2A. This receptor is expressed on cytotoxic lymphocytes, including NK cells and subsets of activated CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 84 publications
4
149
0
2
Order By: Relevance
“…Recent studies in the field of cancer immunotherapy have shown that manipulation of NKG2A signaling can restore NKCC and promote anti-tumor immunity ( 136 , 150 , 151 ). Based on its success, Yaqinuddin and colleagues have proposed mirroring this therapeutic approach for the treatment of COVID-19 patients, where administration of the humanized anti-NKG2A antibody Monalizumab would rejuvenate the anti-viral immune response of COVID-19 patients by counteracting the NKG2A-driven inhibition of NKCC ( 152 ).…”
Section: Pathogen Eliminationmentioning
confidence: 99%
“…Recent studies in the field of cancer immunotherapy have shown that manipulation of NKG2A signaling can restore NKCC and promote anti-tumor immunity ( 136 , 150 , 151 ). Based on its success, Yaqinuddin and colleagues have proposed mirroring this therapeutic approach for the treatment of COVID-19 patients, where administration of the humanized anti-NKG2A antibody Monalizumab would rejuvenate the anti-viral immune response of COVID-19 patients by counteracting the NKG2A-driven inhibition of NKCC ( 152 ).…”
Section: Pathogen Eliminationmentioning
confidence: 99%
“…In this regard, based on the above knowledge, monalizumab, a first-in-class humanized IgG4 targeting the NKG2A receptors expressed on cytotoxic NK and CD8 + T lymphocytes, might be able to release the brake on these cells, leading to the restoration of an adequate antiviral activity through an increase in the production of IFN-γ. 25 Of note, the restoration of NK and CD8 + cell functions could allow a reorganization of the immune cell pool, which is known to undergo a remarkable unsettlement mainly in the severe cases of COVID-19 infection.…”
mentioning
confidence: 99%
“…In conclusion, NKG2A appears to represent another brick in the "COVID-19 wall," owing to its significant involvement in the implementation of adequate immune responses by the host. On this basis, we hypothesize that the anti-NKG2A monoclonal antibody monalizumab, currently under active clinical development for the management of rheumatoid arthritis and several neoplastic disorders, 25 could represent a viable way for treatment of patients with severe COVID-19 infection, characterized by a sudden and marked reduction of the antiviral activity of NK and CD8 + cells.…”
mentioning
confidence: 99%
“…These new aspects of interaction between Sars-Cov-2 S1 protein and the host cells might have important implications in the pathogenesis of COVID19, providing opportunities for developing new therapies against Sars-Cov-2. In particular, counteracting the cellular stress, targeting the S1 protein or using the anti-NKG2A monoclonal antibody monalizumab, currently in use for management of rheumatoid arthritis and several neoplastic disorders 37 , might represent new anti-Sars-Cov-2 strategies to enhance innate immune response at the early stage of the disease, inducing mucosal immunity that might lead to a longterm protection against Sars-Cov-2 infection.…”
Section: Discussionmentioning
confidence: 99%